Luxury or normal goods? Evidence from the utilization of institutional care services for the disabled older adults in China - Xia, Xueqing; Li, Quanlun (Frontiers in Public Health, 2024)
Background: Nursing care is essential for older adults with disabilities. Income plays a crucial role in determining the utilization of institutional care services. Pension benefit, as the main source of income for the older adults in China's cities and towns in their later years, is an important factor influencing the utilization of institutional care services. However, there have been no consistent findings on how pension benefits affect the utilization of institutional care servicse for the disabled older adults.